ACCEPTANCE OF CAMEL MILK AMONG ELEMENTARY SCHOOL STUDENTS IN AL AIN CITY, UNITED ARAB EMIRATES - Hashim, I. B. (Emirates Journal of Food and Agriculture, 2017)
Milk is an important food for children. Although camel is the dominant animal in the U.A.E., camel milk is not commerically available. The objectives of the study were to investigate:1) consumption of milk and dairy products among elementary school students, 2) hedonic rating for sensory characteristics and overall acceptance of camel milk, and 3) effect of flavor on acceptability of camel milk. A questionnaire was designed to provide information on milk and dairy products consumption, milk flavor preference and willingness to participate on a milk tasting test. The questionnaire was distributed to 470 students (boys and girls, grades 4, 5 and 6) at elementary schools (public and private) in Al Ain. Most of the students (93.2%) drink cow milk and only few (9.6%) drink camel milk. Most of the participants drink chocolate (43%) and strawberry-flavored (38.3%) milk. Besides milk, most of the participants consume other diary products (yogurt, liquid yogurt, cheeses and ice-cream). A panel of 173 students was selected to evaluate the milk samples (fresh cow milk , dried cow milk, fresh camel milk and chocolate-flavored camel milk). Sevenpointhedonic scale (smiling faces) was used for rating the color, aroma, taste, texture, and overall acceptance of the milk. Camel milk had the lowest ratings for taste (3.2), aroma (4.1), and overall acceptance (3.8) compared to the fresh cow milk (5.8, 5.9, and 5.8, respectively) and dried cow milk (5.3, 5.7 and 5.5, respectively). Flavoring camel milk with chocolate enhanced all the attributes of the milk specially the taste (6.4), aroma (6.3) and overall acceptance (6.2).